The Relevance of the Multiple Intelligences Approach from the Perspective of Munif Chatib to Islamic Educational Parenting Patterns - Aimatul Khoiriyah; Miasari; Mohammad Nahrowi; Khoiriyah (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to analyze the relevance of the Multiple Intelligences (MI) approach from the perspective of Munif Chatib as developed in his book Sekolahnya Manusia, in relation to parenting patterns within Islamic education. The background of this research stems from the urgent need in modern education to adopt approaches that are more humanistic, personalized, and grounded in fitrah, in alignment with the foundational principles of Islamic education. This study employs a library research method with content analysis techniques applied to the principal works of Munif Chatib, core literature on MI originally formulated by Howard Gardner as well as classical and contemporary references in Islamic education. The main findings indicate a strong coherence between the MI framework and key concepts in Islamic education, such as fitrah, temperament, individuality, and the principles of tarbiyah, particularly in aspects related to potential development, appreciation of diverse intelligences, and adaptive stimulation methods. Furthermore, the study identifies several points of divergence, especially in epistemological dimensions and sources of values.